Kebijakan Pemerintah Daerah Terhadap Dinamika Perjuangan Organisasi Papua Merdeka (OPM) di Kabupaten Puncak Jaya - Wonda, Yuni (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
Organisasi Papua Merdeka (OPM) is considered the group most associated with various forms of community resistance throughout the Papuan landscape. The policy direction of the central and regional governments that ignores the Papuan people is also seen as the source of strengthening the separatist movement. This study uses a qualitative method that seeks to analyze the local government policies of Puncak Jaya Regency regarding the dynamics of the OPM struggle. The results showed that there had been a decrease in OPM sympathizers and members, including deciding to return to the Republic of Indonesia. This reduction was achieved through the Puncak Jaya regency government policy which concentrated on development planning until its realization. Real evidence of development, especially in the interior of Puncak Jaya, makes people feel the state is present in their midst. That the state is not ignorant of them. The most recent policy of the Puncak Jaya regency government is to collect sympathizers or OPM members who wish to join the Republic of Indonesia, provide adequate accommodation, livelihoods and livelihoods, as well as some others are appointed and given the opportunity to become state civil servants. This persuasive approach to development seems to be able to reduce the resistance of the separatist movement (OPM) significantly compared to other military and violent approaches.